Withaferin A protects against spinal cord injury by inhibiting apoptosis and inflammation in mice. (1st January 2017) - Yan, Xianlei; Huang, Guangxiang; Liu, Quan; Zheng, Jiemin; Chen, Hongmou; Huang, Qidan; Chen, Jiakang; Huang, Heqing
Abstract: Context: Withaferin A (WFA) exhibits diverse pharmaceutical applications on human diseases, including rheumatoid arthritis, cancers and microbial infection. Objective: We evaluated the neuroprotective role of WFA using a mouse model of spinal cord injury (SCI). Materials and methods: BALB/c mice were administrated 10 mg/kg of WFA. Gene expression was measured by real-time PCR, western blot and immunohistochemistry. Cell morphology and apoptosis were determined by H&E staining and TUNEL assay. Motor function was evaluated by the BBB functional scale for continuous 7 weeks. Results: WFA significantly improved neurobehavioural function and alleviated histological alteration of spinal cord tissues in traumatized mice. Brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF) significantly increased in WFA-treated mice. Meanwhile, the expression of Nogo-A and RhoA remarkably decreased in the presence of WFA. Furthermore, the apoptotic cell death was attenuated in mice treated with WFA (31.48 ± 2.50% vs. 50.08 ± 2.08%) accompanied by decreased bax and increased bcl-2. In addition, WFA decreased the expression of pro-inflammatory mediators such as IL-1β (11.20 ± 1.96 ng/mL vs. 17.59 ± 1.42 ng/mL) and TNF-α (57.38 ± 3.57 pg/mL vs. 95.06 ± 9.13 pg/mL). The anti-inflammatory cytokines including TGF-β1 (14.32 ± 1.04 pg/mL vs. 9.37 ± 1.17 pg/mL) and IL-10 (116.80 ± 6.91 pg/mL vs. 72.33 ± 9.35 pg/mL) were elevated after WFA administration. Discussion and conclusion: This study demonstrated that WFA has a neuroprotective role by inhibition of apoptosis and inflammation after SCI in mice.